Performance evaluation of short to long term GPS, GLONASS and GPS/GLONASS post-processed PPP. Issue 336 (May 2014) - Yigit, C. O.; Gikas, V.; Alcay, S.; Ceylan, A.
<x content-type="archive" xml:space="preserve">Abstract</x> In recent years, in addition to the GPS constellation, the ability to utilise extra satellites available in the GLONASS system enhanced the capabilities and possible applications of precise point positioning (PPP) method. However, the intrinsic differences between GPS and GLONASS and the lack of a fully tested global tracking network of multi-GNSS systems necessitate the evaluation of their combined use. This paper offers a comprehensive statistical assessment of static PPP using GPS-only, GLONASS-only and GPS/GLONASS combined data. Data analysis is performed in a short (hourly to daily) and a long (several weeks) term, spanning observations from eleven IGS stations. Evaluation of the results reveals insignificant differences in the accuracy and repeatability among the three satellite constellation solutions for long (8 h, 24 h) observation times. The superiority of the combined GPS/GLONASS solution is apparent for short (1 h, 2 h) observation periods, whereas analysis confirms the stability of PPP solutions for the very long (several weeks) observation periods irrespectively of the satellite constellation used.